The Marine Strategy of Russia in the Middle East - A. V. Krylov; N. Z. Shuminov (Сравнительная политика, 2020)
The world media and international discussions at the highest level again are focusing on the Russian’s policy in theMiddle East. This is to a large extent the result of the successful operations of the Russian Aerospace Forces and the Navy inSyria. The article defines the conceptual fundamentals of the modern maritime policy ofRussiain theMiddle East. The authors analyze the main points of the new directions of Russian maritime strategy in the Mediterranean, which were formulated in the following documents: “Fundamentals of the State policy of the Russian Federation in the field of naval activities for the period until2030”, “Marine Doctrine of the Russian Federation” and “Agreement between the Russian Federation and the Syrian Arab Republic on the expansion of the territory of the logistics point of the Navy of the Russian Federation in the vicinity of the port of Tartus”. The participation of the Russian fleets in the military operations in Syria showed that the Russian Navy successfully overcame the systemic crisis and took up positions corresponding to the status of a great power.